Synphilin-1 has neuroprotective effects on MPP+-induced Parkinson's disease model cells by inhibiting ROS production and apoptosis. (18th January 2019) - Shishido, Takeo; Nagano, Yoshito; Araki, Mutsuko; Kurashige, Takashi; Obayashi, Hitomi; Nakamura, Takeshi; Takahashi, Tetsuya; Matsumoto, Masayasu; Maruyama, Hirofumi
Highlights: Synphilin-1 inhibited ROS production and cytochrome c release induced by MPP + in vitro. Synphilin-1 inhibited early steps in the intrinsic apoptotic pathway. Synphilin-1 played a neuroprotective role in Parkinson's disease model cells. Abstract: Synphilin-1, a cytoplasmic protein, interacts with α-synuclein which is one of the main constituents of Lewy bodies and plays an important role in the pathology of Parkinson's disease (PD), in neurons. This interaction indicates that synphilin-1 may also play a central role in PD. However, the biological functions of synphilin-1 are not fully understood, and whether synphilin-1 is neurotoxic or neuroprotective remains controversial. This study examined the function of synphilin-1 in a PD model in vitro. We used an inhibitor of mitochondrial complex I, 1-methyl-4-phenylpyridinium (MPP + ). We established human neuroblastoma SH-SY5Y cell lines that stably expressed human synphilin-1. We found that overexpression of synphilin-1 increased SH-SY5Y cell viability after MPP + treatment. We further found that synphilin-1 significantly suppressed apoptotic changes in nuclei, including nuclear condensation and fragmentation, after MPP + treatment. We showed that synphilin-1 significantly decreased MPP + -induced cleaved caspase-3 and cleaved poly-ADP-ribose polymerase levels by using western blotting. Production of reactive oxygen species (ROS) induced by MPP + was significantly reduced in cells expressing synphilin-1 compared to those expressing empty vector. Synphilin-1 inhibited MPP + -induced cytochrome c release from mitochondria into the cytosol. These data suggested that synphilin-1 may function to protect against dopaminergic cell death by preserving mitochondrial function and inhibiting early steps in the intrinsic apoptotic pathway. Taken together, our results indicated that synphilin-1 may play neuroprotective roles in PD pathogenesis by inhibiting ROS production and apoptosis.